Performance Improvement And User Satisfaction Analysis On Android-Based Educational Mobile Game - Anggy Trisnadoli; Kelvin (International ABEC, 2021)
Tourism is a sector currently in the spotlight by many parties, including the government. This is because tourism attracts tourists. Thus tourism can drive the economy and empower the community. However, the lack of promotion from the government and the community makes tourism in Riau Province less well known. Therefore, in 2016 the educational game "Ayo Wisata ke Riau" was developed, aiming to provide education about tourism in Riau Province. However, the developed game has several problems, such as content that is not up to date and inappropriate, the size of the game is too large, and the display is not attractive. Therefore, a re-engineering process with a User Experience (UX) approach is needed to overcome these problems. After the re-engineering process, Usability testing and User Experience Questionnaires were carried out to test user satisfaction and experience using the application. Testing is done by doing pre-test and post-test. The pre-test is a test by playing games that have been developed in 2016, and a post-test is a test by playing games after the re-engineering process is carried out. Based on the results of the tests carried out, the level of user satisfaction increased by 49.7%, and the results of the evaluation of UX measurements showed positive evaluation results, which meant that users were satisfied in using the application.